2023
DOI: 10.1111/bju.16249
|View full text |Cite
|
Sign up to set email alerts
|

Gender‐affirming care in urology: emergency care of the gender‐affirming surgical patient—what the primary urologist needs to know

Yonah Krakowsky,
Gresha Shah,
Anna‐Lisa V. Nguyen
et al.

Abstract: ObjectiveTo present a narrative review of fundamental information needed to manage postoperative complications in patients who have undergone genital gender‐affirming surgery (GAS).MethodsA narrative review was performed using the following keywords: ‘gender‐affirming surgery’, ‘complications’, ‘emergency’, ‘postoperative’. Articles were included after being reviewed by two primary authors for relevance. Four clinicians with significant experience providing both primary and ongoing urological care to patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
(94 reference statements)
0
1
0
Order By: Relevance
“…Penile implants may also accompany phalloplasties and their complications include infection, erosion, migration, and mechanical failure (46). In a meta-analysis conducted by et al, penile prosthesis complications in phalloplasty were reported as 28% (42).…”
Section: Female-to-male (Ftm) Surgical Procedures and Complicationsmentioning
confidence: 99%
“…Penile implants may also accompany phalloplasties and their complications include infection, erosion, migration, and mechanical failure (46). In a meta-analysis conducted by et al, penile prosthesis complications in phalloplasty were reported as 28% (42).…”
Section: Female-to-male (Ftm) Surgical Procedures and Complicationsmentioning
confidence: 99%